Preparation method of dry-method electrode and battery
Through the solvent-free dry electrode preparation method, high-temperature solid iodine method and ball milling technology, the problems of high energy consumption and process complexity in wet electrode preparation are solved, and efficient and economical electrode preparation is achieved, and the performance and stability of the battery are improved.
Patent Information
- Application Number
- CN202510020552.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-04-11
AI Technical Summary
The existing wet electrode preparation methods have problems such as high energy consumption, low economic benefits, loss of active materials, solvent dependence and process complexity in water-based zinc-iodine batteries, which affect the actual application and long-term performance of the battery.
The solvent-free dry electrode preparation method is adopted, and AC@I2 composite material is prepared by selecting activated carbon as the host material and using high-temperature solid iodine method, and mixed with multi-walled carbon nanotubes, conductive agents and binders, and then ball milled and extruded into a sheet to form a dense and uniform electrode.
The preparation of AC@I2 electrodes is realized by solvent-free mixed dry method, which simplifies the production process, reduces energy consumption and production costs, improves the mechanical strength and electrochemical performance of the electrodes, and the battery exhibits high specific capacity and good cycle stability.
Smart Images

Figure CN119812182A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of batteries, and in particular to a preparation method of a dry electrode and a battery. Background Art
[0002] With the growing demand for reliable and economical energy storage methods, it is particularly important to develop battery technologies with low cost, high safety, long life, low self-discharge and high Coulombic efficiency (CE). 2) batteries have attracted widespread attention due to their high specific capacity (211 mAh / g, based on the mass of iodine), good redox reversibility and abundant iodine ocean reserves (50-60 μg / L). In aqueous batteries, the wet electrode preparation method of iodine cathode has certain advantages in electrode uniformity and mass production, and is often used in electrode preparation. However, the wet electrode preparation faces problems such as low energy consumption and economic benefits, loss of active materials, solvent dependence, and process complexity in the application of iodine cathode in aqueous batteries, which affects its practical application and long-term performance in aqueous batteries. For example, (1) the traditional wet process usually requires the use of organic solvents (such as NMP, etc.) to mix the active material with the binder. The use of organic solvents not only increases the manufacturing cost, but also causes environmental pollution and brings safety hazards, especially when dealing with materials such as iodine that are more sensitive to the environment and health. In the wet process, the solvents used (such as NMP, etc.) need to be recycled. Improper treatment of waste solvents may cause environmental pollution, and the treatment process is complicated, increasing production costs. (2) Iodine has a high solubility in aqueous electrolytes, which will cause iodine to dissolve and diffuse in the electrolyte during the wet electrode preparation process, resulting in the loss of active materials, thereby affecting the energy storage capacity and cycle performance of the electrode. In addition, due to the dissolution of iodine, the electrode structure may change, resulting in decreased stability of the electrode during the cycle and accelerated capacity decay. (3) During the wet preparation process, the binder is usually dissolved in the solvent and mixed with the active material. However, due to the relatively active chemical properties of iodine, it may react with certain organic binders or affect their bonding properties, resulting in unstable electrode structure or decreased electrochemical performance. (4) The wet preparation process requires multiple steps such as dissolution, coating, and drying, which not only increases the complexity of the process, but also places high demands on the equipment, such as coating uniformity and control of solvent volatilization. During the wet coating process, the fluidity of the solution may lead to uneven thickness of the electrode coating, especially when using high concentrations of iodine, it becomes more difficult to control the uniformity of the coating. Surface enrichment, capillary phenomena, drying speed, etc. during the drying process may cause uneven distribution of the binder in the electrode, affecting the mechanical strength and conductivity of the electrode. This inhomogeneity further leads to unstable battery performance. (5) The drying of solvents requires a lot of energy. Especially in large-scale production, the recovery and drying of solvents further increase energy consumption and reduce the overall economic efficiency. Based on the above discussion on wet electrode preparation, it is necessary to invent a solvent-free dry electrode preparation method. Summary of the invention
[0003] The purpose of the present invention is to overcome the above-mentioned deficiencies of the prior art and to provide a method for preparing a dry electrode and a battery.
[0004] To achieve the above-mentioned object of the invention, on the one hand, the present invention provides a method for preparing a dry electrode, comprising:
[0005] Activated carbon was selected as the host material and AC@I was prepared by high temperature iodine fixation method. 2 Composite materials;
[0006] AC@I 2 The composite material, multi-walled carbon nanotubes, conductive agent and binder are mixed in a first mass ratio to form a first mixture; or AC@I 2 The composite material, the multi-walled carbon nanotubes and the binder are mixed in a second mass ratio to form a first mixture;
[0007] The first mixture is transferred to a ball mill container for pulse mixing to obtain a fiberized mixture, the fiberized mixture is extruded, mixed, and pressed into sheets to form pole pieces, the size of the pole pieces is adjusted, and the pole pieces are pressed onto a current collector after adjustment to form a cathode.
[0008] In one embodiment, AC@I is prepared by high temperature iodine solidification method. 2 Composite materials, including:
[0009] The corresponding activated carbon and elemental iodine are weighed according to the third mass ratio, and the elemental iodine and the activated carbon are mixed to form a second mixture; the second mixture is added into a reaction kettle, and heated in an oven at 120° C. for 6 h; after cooling to room temperature, AC@I is obtained. 2 Composite materials.
[0010] In one embodiment, the third mass ratio is 1:1-1.5.
[0011] In one embodiment, the first mass ratio is 85:5:5:5; the second mass ratio is 90:5:5.
[0012] In one embodiment, the first mixture is transferred to a ball mill container for pulse mixing to obtain a fiberized mixture comprising:
[0013] The first mixture is transferred to a ball mill container, and the ball mill is operated at a rotation speed of 150 r / min for 2 minutes each time. After 2 to 3 times of stirring, the mixture is fiberized to obtain a fiberized mixture.
[0014] In one embodiment, the fiberized mixture is extruded, mixed, and pressed into a sheet to form a pole piece, and the size of the pole piece is adjusted, and after adjustment, it is pressed onto a current collector to form a cathode, including:
[0015] The fiberized mixture is squeezed and mixed to agglomerate together, pressed into sheets to form pole pieces, thinned by a roller press, adjusted to a target thickness, and cut into discs of a target diameter, placed on the center of a pretreated current collector, and pressed onto the current collector by a roller press to form a cathode.
[0016] In one embodiment, the target thickness is 100-300 μm.
[0017] In one embodiment, the current collector is ultrasonically cleaned with acetone and anhydrous ethanol for 15 minutes respectively and then dried in a forced air oven; the dried current collector is cut into a circle with a diameter greater than 12 mm to obtain a pretreated current collector, and the current collector is made of stainless steel.
[0018] On the other hand, the present invention provides a battery, wherein the battery has a glass fiber as a separator, a zinc sheet with a diameter of 14 mm as an anode, a cathode prepared by any preparation method in claims 1-8, and an electrolyte of a 2025 type button battery containing 2M zinc sulfate.
[0019] In one embodiment, a 0.1 mm zinc sheet is cleaned with anhydrous ethanol and then cut into discs with a diameter of 14 mm using a cutting machine to make the anode; the diaphragm is a glass fiber disc with a diameter of 16 mm; and the cathode has a diameter of 12 mm.
[0020] The advantages and beneficial effects of the present invention over the prior art are as follows:
[0021] (1) The preparation method of the present invention can realize the preparation of AC@I based on solvent-free mixed dry method 2 electrode.
[0022] (2) The preparation process of the present invention is simple, the raw materials are cheap, and the preparation cycle is short.
[0023] (3) The present invention shortens the production process: no solvent dissolution, coating, drying and other steps are required, and the mixed dry powder is directly pressed into electrodes, which simplifies the production process.
[0024] (4) The traditional wet process requires the use of organic solvents (such as NMP), which has potential pollution to the environment. The dry process in the present invention eliminates the use of solvents and avoids the pollution problem caused by solvent volatilization.
[0025] (5) The dry processing in the present invention can produce dense, uniform and well-integrated electrodes, solving the problems of large energy waste, high cost and environmental pollution, electrode stratification, limited electrode thickness, low mechanical strength, easy cracking and iodine loss caused by the use of PVDF binder.
[0026] (6) The surface loading of iodine in the cathode prepared in the present invention can reach 21.9 mg / cm 2 , surface capacity exceeds 3.5mAh / cm 2 .
[0027] (7) The cathode-assembled full battery prepared by the present invention exhibits high specific capacity and good cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0029] Figure 1 The macroscopic morphology and SEM scanning electron microscope images of the pole piece prepared in Example 1 and the pole piece prepared by the traditional PVDF wet method;
[0030] Figure 2 This is a comparison chart of the cycle performance of the electrode prepared in Example 2 and the electrode prepared by the traditional PVDF wet method;
[0031] Figure 3 This is a diagram of the cycle performance of the battery prepared in Example 3. DETAILED DESCRIPTION
[0032] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0033] Zinc-iodine batteries have attracted much attention due to their high theoretical energy density and specific capacity. Increasing the iodine loading per unit area in the positive electrode to reduce the weight percentage of inactive components is an important way to improve the Zn-I 2 The most direct and effective method to increase the energy density of batteries. The high-load thick electrodes prepared using the traditional slurry wet method have problems such as fracture and delamination, severe volume expansion during the cycle, and slow reaction kinetics. Solving these problems is of great significance for achieving high electrochemical performance of high-iodine content cathodes. The present invention aims to adopt a solvent-free dry processing method, through low-speed intermittent ball milling, to make the fiberized polytetrafluoroethylene binder (PTFE) effectively surround the active material and carbon in an integrated mesh structure, thereby forming a cathode pole piece with a self-supporting membrane and ultimately stable mechanical properties. Then, the dry electrode sheet is laminated on the current collector for use as a cathode. During this period, a carbon-iodine cathode material with high load and excellent electrochemical performance is achieved by changing the iodine content, the ratio of active material to conductive agent, binder, the thickness of the electrode, etc.
[0034] In one aspect, the present invention provides a method for preparing a dry electrode, comprising:
[0035] Step S10: Select activated carbon as the host material and prepare AC@I by high temperature iodine fixation method 2 Composite materials;
[0036] Step S20: AC@I 2 The composite material, multi-walled carbon nanotubes, conductive agent and binder are mixed in a first mass ratio to form a first mixture; or AC@I 2 The composite material, the multi-walled carbon nanotubes and the binder are mixed in a second mass ratio to form a first mixture;
[0037] Step S30: Transfer the first mixture to a ball mill container for pulse mixing to obtain a fiberized mixture, extrude and mix the fiberized mixture, press it into sheets to form pole pieces, adjust the size of the pole pieces, and press them onto a current collector after adjustment to form a cathode.
[0038] Furthermore, AC@I was prepared by high temperature iodine fixation method. 2 Composite materials, including:
[0039] The corresponding activated carbon and elemental iodine were weighed according to the third mass ratio, the elemental iodine was ground into powder in a mortar, and the activated carbon was poured into the powder to form a second mixture; the second mixture was added into a reactor and heated in an oven at 120°C for 6 hours; after cooling to room temperature, AC@I was obtained. 2 Composite materials. If the time is too short, the iodine molecules may not be fully adsorbed into the pores of the activated carbon, resulting in insufficient iodine loading and affecting the electrochemical properties of the material; if the temperature is too low, it will affect the activation degree of the activated carbon pores, thereby reducing its ability to adsorb iodine.
[0040] Furthermore, the third mass ratio is 1:1 to 1.5; by adjusting the ratio above, a high loading amount of elemental iodine is achieved, which is beneficial to increase the specific capacity and area specific capacity of the battery, thereby increasing the energy density of the battery. It can also allow the iodine particles to be fully adsorbed on the surface and pores of the activated carbon; in order to optimize the adsorption performance of the activated carbon, enhance the chemical adsorption effect, and ensure the safety of the operation, the activated carbon and iodine are loaded into the reactor and heated in an oven at a temperature of 120°C for 6 hours.
[0041] Furthermore, the first mass ratio is 85:5:5:5; the second mass ratio is 90:5:5; and subsequently, when the conductive agent is removed, the iodine loading in the electrode is further increased according to the mass ratio of 90:5:5.
[0042] Further, the first mixture is transferred to a ball mill container for pulse mixing to obtain a fiberized mixture, comprising:
[0043] The first mixture is transferred to a ball mill container, and the ball mill is operated at a rotation speed of 150 r / min for 2 minutes each time. After 2 to 3 times of stirring, the mixture is fiberized to obtain a fiberized mixture.
[0044] Further, the fiberized mixture is extruded, mixed, and pressed into a sheet to form a pole piece, and the size of the pole piece is adjusted, and after adjustment, it is pressed onto a current collector to form a cathode, including:
[0045] The fiberized mixture is squeezed and mixed to agglomerate together, pressed into sheets to form pole pieces, thinned by a roller press, adjusted to a target thickness, and cut into discs of a target diameter, placed on the center of a pretreated current collector, and pressed onto the current collector by a roller press to form a cathode.
[0046] Furthermore, the target thickness is 100 to 300 μm.
[0047] The gap between the rollers of the roller press can be adjusted to 0.45mm, the electrode piece can be placed on it and rolled; then the gap can be reduced by 0.03mm each time to 0.3mm, and then reduced by 0.02mm each time to 0.2mm, and then reduced by 0.01mm each time. During the entire decreasing process, the electrode piece is passed through the roller press each time, and the thickness of the electrode piece is adjusted to 100-300μm through the step-by-step rolling and thinning process.
[0048] Furthermore, the current collector is ultrasonically cleaned with acetone and anhydrous ethanol for 15 minutes respectively and then dried in a forced air oven; the dried current collector is cut into a circle with a diameter greater than 12 mm to obtain a pretreated current collector, and the current collector is stainless steel.
[0049] On the other hand, the present invention provides a battery, which has a glass fiber separator, a zinc sheet with a diameter of 14 mm as an anode, a cathode prepared by any of the above preparation methods, and an electrolyte of 2025 type button battery with 2M zinc sulfate.
[0050] Furthermore, the 0.1 mm zinc sheet is cleaned with anhydrous ethanol and then cut into a disc with a diameter of 14 mm by a cutting machine to make an anode; the diaphragm is a glass fiber disc with a diameter of 16 mm; the cathode has a diameter of 12 mm. The diaphragm is one of whatman GF / A, whatman GF / D, Oralky GF / A, and Oralky GF / D.
[0051] The present invention has been tested for many times, and some test results are now cited as references to further describe the invention in detail, and the following is a detailed description in conjunction with specific embodiments.
[0052] Example 1
[0053] Activated carbon and elemental iodine were weighed in a mass ratio of 1:1.2, and elemental iodine and activated carbon were fully mixed to form a mixture. The mixture was added into a reactor and heated in an oven at 120°C for 6 hours. After cooling to room temperature, AC@I was obtained. 2 Composite materials;
[0054] AC@I 2 The composite material, multi-walled carbon nanotubes, super P conductive agent, and PTFE binder were weighed and mixed in a mass ratio of 85:5:5:5 and put into a ball mill. The mill was operated at a speed of 150 r / min and stirred for 2 minutes each time. After three stirrings, the mixture was fiberized to obtain a fiberized mixture. The fiberized mixture was extruded and mixed to agglomerate the mixture together and pressed into sheets to form pole pieces. The pole pieces were rolled and thinned by a roller press to form 150-micron thick pole pieces, which were then scanned by SEM.
[0055] Figure 1 The macroscopic appearance and SEM scanning comparison diagram of the electrode piece prepared in this embodiment and the electrode piece prepared by the traditional PVDF wet method; it is found that the PTFE binder is fibrillated after ball milling to form a uniform fiber network, anchoring the composite material and the conductive agent to form a self-supporting dry electrode membrane, and the electrode surface prepared by rolling is smooth and flat, without cracking, and has a certain flexible structure, which can significantly improve the mechanical strength and electrochemical properties of the electrode; using the traditional PVDF wet method, the thickness uniformity of the electrode piece is difficult to control, especially when preparing thick electrodes, cracking and stratification are prone to occur, causing the electrode to fall off the current collector; and PVDF has poor flexibility and no flexible structure, and is not suitable for the preparation of flexible devices.
[0056] Example 2
[0057] The stainless steel current collector was ultrasonically cleaned with acetone and anhydrous ethanol for 15 minutes respectively and then dried in a blast oven; the dried current collector was cut into a circle with a diameter of 14 mm, and then the edge was flattened by applying external force with a hydraulic press to obtain a pretreated current collector;
[0058] The electrode sheet prepared in Example 1 was cut into 12 mm discs and laminated onto the pretreated current collector to form the cathode; the anode was a zinc sheet with a diameter of 14 mm; the separator was a Whatman GF / A with a diameter of 16 mm. The cathode, anode, and separator were assembled into a full cell in a 2025 battery case, and the electrolyte was 2M zinc sulfate. The full cell was at 0.6-1.6V vs. Zn / Zn 2+ The test was carried out within the voltage window. The cycling performance at a current density of 0.1 A / g was obtained and compared with the full battery prepared by the traditional PVDF as binder process.
[0059] Figure 2The figure is a comparison chart of the cycle performance of the electrode prepared in this embodiment and the electrode prepared by the traditional PVDF wet method; it is found that in the traditional PVDF wet method preparation process, the use and drying of a large amount of N-methyl-2-pyrrolidone (NMP) solvent causes the dissolution and volatilization of iodine, resulting in a decrease in the battery capacity, and its initial discharge specific capacity is only 119mAh / g, and the capacity continues to decay. After 250 cycles, the capacity retention rate is only 85.7%; the initial discharge specific capacity of the electrode prepared by the dry method of the present invention reaches 201mAh / g, and after 500 cycles, it still has a discharge specific capacity of 190mAh / g, and the capacity retention rate is 94.5%. The above shows that the dry method electrode preparation method in the present invention can reduce the loss of iodine and improve the utilization rate of iodine, and its full battery has a higher specific capacity and excellent cycle stability.
[0060] Example 3
[0061] Activated carbon and elemental iodine were weighed in a mass ratio of 1:1.2, and elemental iodine and activated carbon were fully mixed to form a mixture. The mixture was added into a reactor and heated in an oven at 120°C for 6 hours. After cooling to room temperature, AC@I was obtained. 2 Composite materials;
[0062] AC@I 2 The composite material, multi-walled carbon nanotubes and PTFE binder were weighed and mixed in a mass ratio of 90:5:5 and put into a ball mill, and the mixture was operated at a speed of 150 r / min and stirred for 2 minutes each time. After three stirrings, the mixture was fiberized to obtain a fiberized mixture, and the fiberized mixture was extruded and mixed to agglomerate together, and pressed into a sheet to form a pole piece, and the pole piece was rolled and thinned by a roller press to form a pole piece with a thickness of 300 microns;
[0063] The stainless steel current collector was ultrasonically cleaned with acetone and anhydrous ethanol for 15 minutes respectively and then dried in a blast oven; the dried current collector was cut into a circle with a diameter of 14 mm, and then the edge was flattened by applying external force with a hydraulic press to obtain a pretreated current collector;
[0064] The 300 micron thick electrode sheet was cut into 12 mm discs and laminated onto the pre-treated current collector to form the cathode; the anode was a zinc sheet with a diameter of 14 mm; the separator was a Whatman GF / A with a diameter of 16 mm. The cathode, anode, and separator were assembled into a full cell in a 2025 battery case, and the electrolyte was 2M zinc sulfate. The full cell was 0.6-1.6V vs. Zn / Zn 2+ The test was carried out within the voltage window of 100A / g. The cycle performance diagram at a current density of 0.05A / g was obtained.
[0065] Figure 3The electrode cycle performance diagram prepared in this example is shown in Figure 2. It is found that the full battery assembled based on the electrode prepared in this invention has a cycle performance of 21.9 mg / cm 2 The high iodine loading still shows excellent discharge specific capacity, and its surface capacity exceeds 3.5 mAh / cm 2 , which has significant commercial application value.
[0066] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a dry electrode, characterized in that: include: Activated carbon was selected as the host material, and the AC@I2 composite material was prepared by high-temperature iodine fixation method; The AC@I2 composite material is mixed with multi-walled carbon nanotubes, a conductive agent and a binder in a first mass ratio to form a first mixture; or the AC@I2 composite material is mixed with multi-walled carbon nanotubes and a binder in a second mass ratio to form a first mixture; The first mixture is transferred to a ball mill container for pulse mixing to obtain a fiberized mixture, the fiberized mixture is extruded, mixed, and pressed into sheets to form pole pieces, the size of the pole pieces is adjusted, and the pole pieces are pressed onto a current collector after adjustment to form a cathode.
2. The method for preparing a dry electrode according to claim 1, characterized in that: The AC@I2 composite material is prepared by a high temperature iodine solidification method, including: The corresponding activated carbon and elemental iodine are weighed according to the third mass ratio, and the elemental iodine is mixed with the activated carbon to form a second mixture; the second mixture is added into a reactor and heated in an oven at a temperature of 120° C. for 6 hours; after cooling to room temperature, an AC@I2 composite material is obtained.
3. The method for preparing a dry electrode according to claim 2, characterized in that: The third mass ratio is 1:1-1.
5.
4. The method for preparing a dry electrode according to claim 1, characterized in that: The first mass ratio is 85:5:5:5; the second mass ratio is 90:5:
5.
5. The method for preparing a dry electrode according to claim 1, characterized in that: The first mixture is transferred to a ball mill container and pulse mixed to obtain a fiberized mixture comprising: The first mixture is transferred to a ball mill container, and the ball mill is operated at a rotation speed of 150 r / min for 2 minutes each time. After 2 to 3 times of stirring, the mixture is fiberized to obtain a fiberized mixture.
6. The method for preparing a dry electrode according to claim 1, characterized in that: The fiberized mixture is extruded, mixed, and pressed into sheets to form a pole sheet, and the size of the pole sheet is adjusted. After adjustment, the pole sheet is pressed onto a current collector to form a cathode, including: The fiberized mixture is squeezed and mixed to agglomerate together, pressed into sheets to form pole pieces, thinned by a roller press, adjusted to a target thickness, and cut into discs of a target diameter, placed on the center of a pretreated current collector, and pressed onto the current collector by a roller press to form a cathode.
7. The method for preparing a dry electrode according to claim 6, characterized in that: The target thickness is 100 to 300 μm.
8. The method for preparing a dry electrode according to claim 6, characterized in that: The current collector is ultrasonically cleaned with acetone and anhydrous ethanol for 15 minutes respectively and then dried in a forced air oven; the dried current collector is cut into a circle with a diameter greater than 12 mm to obtain a pretreated current collector, which is made of stainless steel.
9. A battery, characterized in that: The battery uses glass fiber as a diaphragm, a zinc sheet with a diameter of 14 mm as an anode, a cathode prepared by any preparation method in claims 1-8, and an electrolyte of a 2025-type button battery containing 2M zinc sulfate.
10. The battery according to claim 9, characterized in that The 0.1 mm zinc sheet was cleaned with anhydrous ethanol and then cut into discs with a diameter of 14 mm using a cutting machine to make the anode; the diaphragm was a glass fiber disc with a diameter of 16 mm; and the cathode had a diameter of 12 mm.